A case of adult osteomyelitis in a Final Late Holocene hunter-gatherer population, eastern Pampa–Patagonian transition, Argentina - Flensborg, Gustavo Ariel (2013)
Osteomyelitis was frequent in prehistoric times, although its paleopathological recognition and analysis in skeletal remains is typically incomplete. Contrasting with osteomyelitis in children, in adults it is usually a subacute or chronic infection that develops secondary to an open injury. The aim of this paper is to present a case of osteomyelitis in an adult female skeleton, from a hunter-gatherer population that inhabited the eastern Pampa–Patagonian transition (Argentina) during Final Late Holocene (ca. 250 years BP). Macroscopic studies as well as biplanar radiographs and CT scans were used for diagnosis. Lamellar bone formations on the diaphysis and in the interior of the marrow cavity were recorded. Also, a lytic lesion was identified in CT images. The diagnostic procedures and the probable causes that could generate the lesions in the long bones of the lower limb are discussed. The lesions are consistent with osteomyelitis secondary to a contiguous focus of infection, possibly linked to the abscess in the maxillary bone.